Contract Termination from a Civil Law Perspective: A Review of Mechanisms, Types, and Legal Implications - Alfi Syahrin Niza Raja Rambe; Fauzan Lubis; Muhammad Mikail Harahap; Khairunnisa Siregar (ISNU Sumatera Utara, 2024)
This study examines the deposit agreement in two legal systems applicable in Indonesia, namely the Civil Code (KUHPerdata) and the Compilation of Sharia Economic Law (KHES). The deposit agreement is a form of trust between the owner of the goods and the recipient of the deposit that has legal consequences. This study uses a normative juridical method with a comparative legal approach to analyze the similarities and differences in the provisions of the deposit in both legal systems. The results show that the Civil Code regulates the deposit of goods in Book III Chapter XI Articles 1694-1739, while the KHES regulates it in Chapter XIV concerning Wadi'ah. Both systems have similarities in terms of the obligation of the recipient of the deposit to maintain and return the goods in their original condition, but there are fundamental differences in the aspect of providing compensation and the responsibilities of the recipient of the deposit. The Civil Code allows for deposit with payment, while the KHES regulates wadi'ah as a tabarru' contract that is mutual in nature. This study contributes to a comprehensive understanding of the legal dualism of deposit in Indonesia that can be used as a reference in business practices and dispute resolution.